CEDRELA NGOBE (MELIACEAE), A NEW SPECIES FROM PANAMA AND COSTA RICA. (1st July 2015) - Köcke, A. V.; Muellner-Riehl, A. N.; Cáceres, O.; Pennington, T. D.
Abstract : We present a new species of Meliaceae, Cedrela ngobe Köcke, T.D.Penn. & Muellner, from Panama and Costa Rica. A detailed description with illustrations and a distribution map are provided. Based on distribution data and climatic niche modelling, the species is classified as Vulnerable according to IUCN Red List categories.